3D Conformal Surface Engineering of Continuous Fibers with Porous Microstructures for 1D Advanced Functional Materials. Issue 4 (3rd March 2021) - Gong, Jianliang; Xu, Bingang
Abstract: One‐dimensional (1D) continuous advanced functional materials and devices with inherent flexibility for complex deformations facilitate a broad range of applications in wearable technology. This communication presents a new electrostatic self‐assembly strategy for controllable assembly of nanomaterials to fabricate 1D continuous materials with customizable functions based on a kind of continuous fiber fully surface‐engineered with 3D conformal porous microstructures (F@3CPMs) by a unique self‐assembly approach of breath figure using water microdroplet arrays. Through gently rubbing the modified fibers with suitable triboelectric materials, either positively or negatively charged F@3CPMs can be rationally prepared with adjustable triboelectric charge intensity. Besides showing superiority in incorporating desired components, such kind of F@3CPMs are demonstrated to have general applicability and enhanced performance in controllable self‐assembly of polymeric, metal, and carbon nanomaterials for customizable functionalizations. Moreover, taking advantages of continuous fibers that can deform largely, functional F@3CPMs are further applied for development of 1D flexible motion sensing devices by twisting directly, which can be either used as 1D freestanding devices for straightforward integration with conventional fabrics or woven as a fabric structure integrity for a kind of self‐powered interactive textiles without additional battery as power resources to detect and monitor the body motions of human beings. Abstract : A new electrostatic self‐assembly strategy for controllable assembly of nanomaterials based on a kind of fiber surface‐engineered with 3D conformal porous microstructures is developed to fabricate 1D continuous advanced functional materials and devices for interactive textiles by either sewing or weaving to detect and monitor human body motions.